Cannabinoid receptor 2 selective agonist ameliorates adjuvant-induced arthritis by modulating the balance between Treg and Th17 cells - Tian, Na; Yang, Cui; Du, Yu; Chen, Miao; Li, Bin; Li, Dan; Dai, Sheng-Ming (Frontiers in Pharmacology, 2025)
BackgroundAdjuvant-induced arthritis (AIA) serves as a classic model for rheumatoid arthritis (RA), typified by inflammatory cell infiltration and joint damage. This study explores the therapeutic efficacy of HU-308, a CB2 receptor-specific agonist, on inflammation and immune balance in AIA.MethodsAIA was induced in mice by CFA injection. AIA mice were treated with HU-308 or vehicle, and effects on paw swelling, spleen index, histopathology, and immune cell profiles were evaluated. Flow cytometry, in vitro differentiation assays, and Western blot analysis were performed to examine Th17 and Treg cells, as well as signaling pathways involved in their differentiation.ResultsHU-308 reduced paw swelling, lowered spleen index, and preserved joint integrity in AIA mice, mitigating inflammatory cell infiltration and bone erosion. Flow cytometry revealed that HU-308 restored the Th17/Treg imbalance in AIA, decreasing Th17 cell frequency and enhancing Treg cell infiltration. In vitro assays confirmed HU-308s role in promoting Treg differentiation and inhibiting Th17 polarization. Western blot analysis indicated that HU-308 modulated immune balance through the JAK/STAT5 and TGF-β/SMAD signaling pathways, increasing Foxp3 and TGF-β expression.ConclusionHU-308 demonstrates significant anti-inflammatory effects in AIA by restoring Th17/Treg balance and reducing joint damage. The findings indicate that HU-308 holds potential as an immunomodulatory agent for RA, providing valuable insights into CB2-mediated therapeutic strategies for autoimmune diseases.